Comparative Analysis of The Students’ Speaking Anxiety Level at English Study Program of UKI Toraja - Gayatri, Nina; Tulaktondok, Linerda; Sallata, Yizrel Nani (Universitas Cokroaminoto Palopo, 2023)
This study investigates the speaking anxiety levels among students enrolled in the English Study Program at UKI Toraja, motivated by a noticeable reluctance among students to engage in speaking competitions and public speaking events. The research seeks to determine whether there are significant differences in speaking anxiety levels across students from different academic semesters. A quantitative approach was used to assess these levels, with participants comprising 15 first-semester students, 8 third-semester students, 15 fifth-semester students, and 23 seventh-semester students. The data were collected through an 18-item questionnaire designed to evaluate common indicators of speaking anxiety, including cognitive, emotional, and physiological symptoms that typically occur during speaking tasks. The analysis was conducted using One-Way Analysis of Variance (ANOVA) through Microsoft Excel to identify whether the variations in anxiety across semesters were statistically significant. The findings revealed substantial differences in anxiety levels among the students. For the low level of anxiety, the analysis produced a p-value of 5.42E-14, indicating a statistically significant difference. Similarly, for the moderate level of speaking anxiety, the p-value was 4.19E-12, and for the high level, the p-value was 2.62E-14, both below the standard significance threshold of 0.05. These results confirm that students’ speaking anxiety does indeed vary significantly across academic semesters, suggesting that anxiety may decrease or shift in nature as students progress through their studies. However, the persistence of high anxiety in some advanced students also suggests that academic experience alone may not be sufficient to eliminate anxiety without targeted support. In conclusion, this study contributes to the broader understanding of speaking anxiety in EFL contexts by highlighting its variation based on semester level, thus emphasizing the need for semester-specific pedagogical strategies, early intervention, and continuous support to help learners overcome their anxiety and enhance their oral communication competence throughout their academic journey.